A conductive sodium alginate and carboxymethyl chitosan hydrogel doped with polypyrrole for peripheral nerve regeneration - Bu, Ying; Xu, Hai-Xing; Li, Xin; Xu, Wen-Jin; Yin, Yi-xia; Dai, Hong-lian; Wang, Xiao-bin; Huang, Zhi-Jun; Xu, Pei-Hu (RSC advances, 2018)
Polymer materials with electrically conductive properties have good applications in their respective fields because of their special properties. However, they usually exhibited poor mechanical properties and biocompatibility. In this work, we present a simple approach to prepare conductive sodium alginate (SA) and carboxymethyl chitosan (CMCS) polymer hydrogels (SA/CMCS/PPy) that can provide sufficient help for peripheral nerve regeneration. SA/CMCS hydrogel was cross-linked by calcium ions provided by the sustained release system consisting of d -glucono-δ-lactone (GDL) and superfine calcium carbonate (CaCO 3 ), and the conductivity of the hydrogel was provided by doped with polypyrrole (PPy). Gelation time, swelling ratio, porosity and Young's modulus of the conductive SA/CMCS/PPy hydrogel were adjusted by polypyrrole content, and the conductivity of it was within 2.41 × 10 −5 to 8.03 × 10 −3 S cm −1 . The advantages of conductive hydrogels in cell growth were verified by controlling electrical stimulation of cell experiments, and the hydrogels were also used as a filling material for the nerve conduit in animal experiments. The SA/CMCS/PPy conductive hydrogel showed good biocompatibility and repair features as a bioactive biomaterial, we expect this conductive hydrogel will have a good potential in the neural tissue engineering. Polymer materials with electrically conductive properties have good applications in their respective fields because of their special properties.